2019
DOI: 10.1042/bsr20191965
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated circPAPPA suppresses the proliferation and invasion of trophoblast cells via the miR-384/STAT3 pathway

Abstract: Preeclampsia (PE) is the main cause of maternal death in primipara, and commonly results in severe maternal and neonatal complications such as multiple organ dysfunction syndrome. However, the exact pathogenesis of this disease remains unclear. Circular RNAs (circRNAs) are noncoding RNAs that have been shown to be extensively involved in numerous physiological processes, but there is limited knowledge of their functions and mechanisms in PE. In the present study, we found the expression of a circRNA, hsa_circ_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…They identified ATF4/miR-214/circRNA7964 and TCF7/miR-22-3p/circRNA16347 as two competing endogenous networks by bioinformatic analysis (Shen et al, 2018). In addition, circPAPPA and circTRNC18 play regulatory roles in trophoblast cells (Shen et al, 2019;Zhou et al, 2019) and a subset of placental cells, thus performing critical functions in fetal growth and survival. These results indicate that circRNAs may play key regulatory roles in FGR.…”
Section: Introductionmentioning
confidence: 99%
“…They identified ATF4/miR-214/circRNA7964 and TCF7/miR-22-3p/circRNA16347 as two competing endogenous networks by bioinformatic analysis (Shen et al, 2018). In addition, circPAPPA and circTRNC18 play regulatory roles in trophoblast cells (Shen et al, 2019;Zhou et al, 2019) and a subset of placental cells, thus performing critical functions in fetal growth and survival. These results indicate that circRNAs may play key regulatory roles in FGR.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Deng et al found that has_circ_0011460 might be a novel potential therapeutic target for severe PE treatment using RNA sequencing [7]. Zhou et al [8] reported that circRNA pregnancy-associated plasma protein A (circPAPPA) was down-regulated in PE placenta, and its deficiency hampered trophoblast cell proliferation and invasion . Shen et al [9] manifested that circRNA trinucleotide repeat containing 18 (circTNRC18) was up-regulated in PE placenta, and a high circTNRC18 expression repressed the migration and epithelial-mesenchymal transition (EMT) of trophoblast cells in PE.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Moreover, miR-384, targeted by circPAPPA, affected the development of trophoblast cells. 32 Besides, many long non-coding RNAs (lncRNAs), including SNHG3, 33 TUG1, 34 and NEAT1, 35 were revealed to target miR-384 in cancer development. However, the relationship between circ_0020123 and miR-384 in NSCLC remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%